New Variant of MELAS Syndrome With Executive Dysfunction, Heteroplasmic Point Mutation in the MT-ND4 Gene (m.12015T>C; p.Leu419Pro) and Comorbid Polyglandular Autoimmune Syndrome Type 2 - Endres, Dominique; Süß, Patrick; Maier, Simon J.; Friedel, Evelyn; Nickel, Kathrin; Ziegler, Christiane; Fiebich, Bernd L.; Glocker, Franz X.; Stock, Friedrich; Egger, Karl; Lange, Thomas; Dacko, Michael; et al. (Frontiers in Immunology, 2019)
Background: Mitochondrial diseases are caused by dysfunctions in mitochondrial metabolic pathways. MELAS syndrome is one of the most frequent mitochondrial disorders; it is characterized by encephalopathy, myopathy, lactic acidosis, and stroke-like episodes. Typically, it is associated with a point mutation with an adenine-to-guanine transition at position 3243 of the mitochondrial DNA (mtDNA; m.3243A>G) in the mitochondrially encoded tRNA leucine 1 (MT-TL1) gene. Other point mutations are possible and the association with polyglandular autoimmune syndrome type 2 has not yet been described. Case presentation: We present the case of a 25-year-old female patient with dysexecutive syndrome, muscular fatigue, and continuous headache. Half a year ago, she fought an infection-triggered Addison crisis. As the disease progressed, she had two epileptic seizures and stroke-like episodes with hemiparesis on the right side. Cerebral magnetic resonance imaging showed a substance defect of the parieto-occipital left side exceeding the vascular territories with a lactate peak. The lactate ischemia test was clearly positive, and a muscle biopsy showed single cytochrome c oxidase-negative muscle fibers. Genetic testing of blood mtDNA revealed a heteroplasmic base exchange mutation in the mitochondrially encoded NADH:ubiquinone oxidoreductase core subunit 4 (MT-ND4) gene (m.12015T>C; p.Leu419Pro; heteroplasmy level in blood 12%, in muscle tissue: 15%). The patient suffered from comorbid autoimmune polyglandular syndrome type 2 with Hashimoto's thyroiditis, Addison's disease, and autoimmune gastritis. In addition, we found increased anti-glutamic acid decarboxylase 65, anti-partial cell, anti-intrinsic factor, and anti-nuclear antibodies. Conclusion: We present an atypical case of MELAS syndrome with predominant symptoms of a dysexecutive syndrome, two stroke-like episodes, and fast-onset fatigue. The symptoms were associated with a not yet described base and aminoacid exchange mutation in the MT-ND4 gene (m.12015T>C to p.Leu419Pro). The resulting changed protein complex in our patient is part of the respiratory chain multicomplex I and might be the reason for the mitochondriopathy. However, different simulations for pathogenetic relevance are contradictory and rather speak for a benign variant. To our knowledge this case report is the first reporting MELAS syndrome with comorbid polyglandular autoimmune syndrome type 2. Screening for autoimmune alterations in those patients is important to prevent damage to end organs.